2011
DOI: 10.1088/0004-637x/738/2/140
|View full text |Cite
|
Sign up to set email alerts
|

On the Reliability of Stellar Ages and Age Spreads Inferred From Pre-Main-Sequence Evolutionary Models

Abstract: We revisit the problem of low-mass pre-main-sequence stellar evolution and its observational consequences for where stars fall on the Hertzsprung-Russell diagram (HRD). In contrast to most previous work, our models follow stars as they grow from small masses via accretion, and we perform a systematic study of how the stars' HRD evolution is influenced by their initial radius, by the radiative properties of the accretion flow, and by the accretion history, using both simple idealized accretion histories and his… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
157
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(167 citation statements)
references
References 51 publications
7
157
0
Order By: Relevance
“…This is an important point to emphasize because the inclusion of these processes affects the evolution of pre-MS models introducing additional sources of uncertainty (see e.g., Pinsonneault et al 1990;D'Antona et al 2000;Siess 2001;Stahler & Palla 2004;Baraffe et al 2009;Hosokawa et al 2011).…”
Section: The Modelsmentioning
confidence: 99%
“…This is an important point to emphasize because the inclusion of these processes affects the evolution of pre-MS models introducing additional sources of uncertainty (see e.g., Pinsonneault et al 1990;D'Antona et al 2000;Siess 2001;Stahler & Palla 2004;Baraffe et al 2009;Hosokawa et al 2011).…”
Section: The Modelsmentioning
confidence: 99%
“…Among the drawbacks, the intrinsic faintness of TOns compared to the MSTOs makes TOns prone to photometric errors and incompleteness, issues that are exacerbated in the UV CMD because older TOns tend to be also redder. From the theoretical side, the TOn visibility is intimately connected with the PMS evolutionary times, which are still model dependent (see, e.g., Baraffe et al 2009;Hosokawa et al 2011;Soderblom et al 2014, p. 219 and references therein).…”
Section: Stellar Clocks: Ms Turn-off and Pms Turn-onmentioning
confidence: 99%
“…Impact of the mass of Larson's second core for early protostar evolution Baraffe et al (2009) and Baraffe & Chabrier (2010) showed that episodic accretion on a newborn protostar provides a plausible explanation for the observed luminosity spread in young stellar clusters and star forming regions without invoking any age spread and can also explain unexpectedly high depletion levels of lithium that have been observed in some young objects. This scenario was questioned by Hosokawa et al (2011) who argued that the scenario could not hold in the lower (T eff 3500 K) part of the Hertzsprung-Russell diagram. The issue has been addressed in detail in Baraffe et al (2012), where the authors have shown that the only reason why Hosokawa et al (2011) could not reproduce the observed luminosity spread in the aforementioned domain stems from their assumed value for the second Larson core mass (i.e.…”
Section: Varying the Initial Parametersmentioning
confidence: 99%